2021
DOI: 10.1155/2021/2342784
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulating hsa-miR-128a Increased the Effects of Pembrolizumab on Laryngeal Cancer Cells via the p53 Pathway

Abstract: Objectives. Recently, immunotherapy and microRNA have shown much more promises in oncology research, inspiring new hope for a cure for various malignancies. Specifically, the function and mechanisms of action of pembrolizumab have been investigated in many cancers, but not in laryngeal squamous cell carcinoma. The present study thus focused on the effect of hsa-miR-128a on pembrolizumab in laryngeal cancer cells as well as tried to elucidate the mechanisms that may mediate this effect. Methods. Hep2 and AMC-HN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…This finding has been supported by study done by Rasmussen et al 2020, that documented significant correlations between IHC biomarkers p53 and PD-L1 (17). Also other study obtained by Hui Chen et al 2021 that refer to this correlation (18).…”
Section: The Correlation Between the Expression Of Pdl1 P53 And Ki67 ...supporting
confidence: 53%
“…This finding has been supported by study done by Rasmussen et al 2020, that documented significant correlations between IHC biomarkers p53 and PD-L1 (17). Also other study obtained by Hui Chen et al 2021 that refer to this correlation (18).…”
Section: The Correlation Between the Expression Of Pdl1 P53 And Ki67 ...supporting
confidence: 53%
“…In addition, the role of FOXD2-AS1 in HNSCC was also related to the p53 signaling pathway, and the p53 signaling pathway plays a part in the regulation of expression of several genes and is closely related to the development of human tumors, whose activation initiates cell cycle arrest as well as DNA repair, and inhibits proliferation of OSCC cells [ 38 ]. Overexpression of hsa-miR-128a-mediated p53 signaling pathway increases the role of Pembrolizumab in Laryngeal Squamous Cell Carcinoma Cell lines [ 39 ]. The findings of the current study confirmed that FOXD2-AS1 is elevated in HNSCC tissues and is a potential predictor of HNSCC in patients, thereby promoting the proliferation of HNSCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…AMC-HN8 (RRID: CVCL_5966) and TU212 (RRID: CVCL_4915) human LSCC cells [ 20 , 23 25 ] were kindly provided by the BeNa Culture Collection (Jiangsu, China). Cells were cultured in high glucose Dulbecco’s modified Eagle medium (DMEM) with 10% foetal bovine serum (PAN-Biotech, Adenbach, Germany) and incubated in a humidified 37 °C incubator with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%